ACESSO À LINHA DE CUIDADOS, CAPITAL SOCIAL E MULTIMORBIDADE COMPLEXA: Um estudo com usuários de serviços de hemodiálise em região metropolitana de uma capital no sudeste brasileiro - Soares, Ana Cristina de Oliveira (2022)
Introduction: End-stage renal disease is a public health problem, demanding highcomplexity care such as hemodialysis, however, few studies assess access, social capital and complex multimorbidity of users of hemodialysis services. Objectives: To analyze factors associated with access to hemodialysis services, social capital and complex multimorbidity among individuals undergoing hemodialysis treatment in the Greater Vitória Metropolitan Region - RMGV. Method: Analytical cross-sectional epidemiological census with 1024 individuals. Data collection took place from February to September 2019. For access, dimensions were analyzed: accessibility, availability and acceptability. Social capital was categorized into: cognitive, structuring and underlying with data collected using the Integrated Questionnaire to Measure Social Capital. Complex multimorbidity was characterized by the occurrence of three or more chronic diseases affecting three or more organ systems. Data were analyzed by descriptive statistics and multinomial (access and social capital) and binary (complex multimorbidity) logistic regression. Results: Mean age was 54.7+0.59 years, predominant age group between 30 and 59 years (n=528, 51.6%). Most men (n=581, 56.7%), up to 8 years of schooling (n=523, 51.1%), self-declared brown/black (n=737, 72%), income less than or equal to two minimum wages (n=555, 56.2%), retired or away from work, receiving social benefits (n =547, 54.2%) and residing in the same city where hemodialysis was performed (n =642, 62.8%). 25.1% (n=209) were at the highest level of access and the factors that increased the chances of the lowest level of access were: age group between 30 and 59 years (OR 2.16, 95% CI 1.377 –3.383), women (OR 1.74, 95% CI 1.11–2.72) and income less than or equal to two minimum wages (OR 1.80, 95% CI 1.17–2.76). Mean ESF coverage factors (OR 0.54, 95% CI 0.29–0.99), no previous conservative treatment (OR 0.59, 95% CI 0.38–0.91), lack of paid work ( OR 0.35, 95% CI 0.15–0.85), retirement/sick leave (OR 0.27, 95% CI 0.12– 0.64) and poor or very poor self-rated health (OR 0, 62, 95% CI 0.40–0.96) reduced the odds of the lowest access. For social capital, low income was associated with greater chances of lower total social capital (OR 1.62; 95%CI 1.03–2.54) and cognitive (OR 1.71; 95%CI 1.14–2.56) ), while a low level of access was associated with greater chances of lower social capital in all dimensions: total (OR 2.30, 95%CI 1.32–4.01), cognitive (OR 1.78; 95%CI 1 .04-3.04), structuring (OR 1.86; 95%CI 1.08-3.21) and underlying (OR 2.17; 95%CI 1.25-3.76). 81% (n=815) had complex multimorbidity. Low General Mortality Index in the municipality (OR 0.395; 95%CI 0.179–0.870), age between 19 and 29 years (OR 0.402; 95%CI 0.196-0.825), more than eight years of schooling (OR 0.536; 95%CI 0.29– 0.966) and positive self-rated health (OR 0.446; 95%CI 0.301–0.661) reduced the chances of Complex Multimorbidity. Hemodialysis for less than two years increased the chance of Complex Multimorbidity (OR 1.779; 95%CI 1.057- 2.997). Conclusion: Contextual, individual characteristics and health behaviors influence access to services, social capital and complex multimorbidity among hemodialysis users in the RMGV. Keywords: Access to health services; share capital; complex multimorbidity; hemodialysis.